1985
DOI: 10.1007/bf00964572
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the binding of optically pure (?)- and (+)-[3H]nicotine to rat brain membranes

Abstract: A comparison of the binding of (-)- and (+)-[3H]nicotine to rat brain membranes revealed that only the (-)-enantiomer showed high affinity binding; while the (+)-enantiomer was at least 1/10 as effective as the (-)-enantiomer when in competition with (-)-[3H]nicotine as the ligand. Positive cooperativity, which is observed with (-)-[3H]nicotine in the presence of low concentrations of (+)-nicotine, may account for the seeming paradox.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…These observations agree with the findings of Marks and Collins (1982) for t3H]nicotine binding to mouse brain. Similar KD values for a high-affinity site in rat brain have been reported (Romano and Goldstein, 1980; Sershen et al, 198 1; Costa and Murphy, 1983; Hayashi et al, 1984; London et al, 1985), although other workers have found higher affinities (Yoshida et al, 1982; Clarke et al, 1984; Sloan et al, 1984;Abood et al, 1985; Benwell and Balfour, 1985). Analysis of the inhibition of [3H]nicotine binding by unlabelled nicotine over a greater concentration range ( 10-3-10-'0 M ) resulted in a Ki value for (-)-nicotine of 6 X M(Tab1e 2), which is in reasonable agreement with the apparent KD.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These observations agree with the findings of Marks and Collins (1982) for t3H]nicotine binding to mouse brain. Similar KD values for a high-affinity site in rat brain have been reported (Romano and Goldstein, 1980; Sershen et al, 198 1; Costa and Murphy, 1983; Hayashi et al, 1984; London et al, 1985), although other workers have found higher affinities (Yoshida et al, 1982; Clarke et al, 1984; Sloan et al, 1984;Abood et al, 1985; Benwell and Balfour, 1985). Analysis of the inhibition of [3H]nicotine binding by unlabelled nicotine over a greater concentration range ( 10-3-10-'0 M ) resulted in a Ki value for (-)-nicotine of 6 X M(Tab1e 2), which is in reasonable agreement with the apparent KD.…”
Section: Discussionsupporting
confidence: 77%
“…Marks and Collins (1 982) suggested that (+)-nicotine binds almost exclusively to the low-affinity site. In a recent comparison of the binding of the tritiated enantiomers of nicotine to rat brain membranes, Abood et al (1985) found that (-)-[3H]nicotine labelled two sites with nanomolar or subnanomolar affinities, whereas (+)-[3H]nicotine did not exhibit any high-affinity specific binding at physiological pH. (At pH 8.5, the unnatural enantiomer labelled one site with nanomolar affinity.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine is not only a ligand tracer exhibiting affinity to acetylcholine-nicotinic receptors in brain, but also an excellent tracer for measuring CBF (Ohno et al 1979;Suzuki et al 1983;Tomida et al 1987Tomida et al , 1989. The 3H-labelled (S)-(-)enantiomer of nicotine showed high affinity of binding to the membrane of acetylcholine-nicotinic receptor cells in rat brain, while specific binding of 3H-labelled (R)-( + )nicotine is not found at pH 7.5 (Abood et al 1985). If 11C-labelled (S)-nicotine is used as a tracer, it is distributed in three compart- merits, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Lastly, 3H-nicotine was found to be an excellent diffusion tracer for measurement of CBF (Ohno et al 1979;Suzuki et al 1983;Tomida et al 1987Tomida et al , 1989 because the brain uptake index (BUI) for nicotine is higher than that for water (Bradbury et al 1975). Prior to the attempt to assay specific binding of l~C-(S)nicotine, which binds to nicotinic receptors in human brain, we used t 1C_(R)nicotine, which does not bind to nicotinic receptors (Abood et al 1985), as a diffusion tracer to measure CBF in normal volunteers and to compare CBF values obtained with 11C-(R)nicotine by means of PET with CBF values obtained using the C 150 2 inhalation steadystate method (Frackowiak et al 1980).…”
Section: Introductionmentioning
confidence: 99%